‘HACKERS OF FAITH’: DECODING THE END-TO-END ENCRYPTION OF CULT-CODE-CREED - Attumkal, Mathew (Journal of Dharma, 2024)
The notion of ’faith-hacking’ has crystallized in my mind, stirred by contemporary discussions on the interplay between modern techno-centric knowledge and spiritually illumined wisdom. This metaphorical use of "hacker" highlights a dynamic approach to faith-centred research, one that revitalizes spiritual practices and poses significant ethical questions through creative and critical engagement with religious doctrines. Unlike conventional hackers who breach computer systems and compromise cybersecurity, a faith hacker or religious hacker explores the depths of religious doctrines, texts, and traditions, using creativity and critical thinking to reinterpret and innovate within their spiritual frameworks.